Health-related quality of life of HIV-infected intravenous drug users. (November 2013) - Surah, S; Adams, R; Townsend, L; Reynolds, I; Kinahan, JC; Keating, S; Mulcahy, F; Keenan, E; Barry, M; Lyons, F
To investigate health-related quality of life in HIV-infected intravenous drug users registered but not engaged in HIV outpatient care (missing ≥2 outpatient appointments over 1 year or non-attendance for ≥6 months) we conducted a cross-sectional study to examine health-related quality of life of HIV-infected intravenous drug users registered for care at an inner city HIV unit. EQ-5D, SF-36, SF-6D, mood disorder, clinical and substance misuse data were collected. Mean scores and preference derived utility scores were calculated. Statistical relationships between health-related quality of life and other variables were explored using univariate and multivariate analysis. Fifty-five patients were recruited, 64% were males. The mean anxiety value was 11.44 (anxious) and mean depression score was 9.3 (borderline depressed). The mean EQ-5D utility was 0.45 (95% CI 0.35, 0.55) and mean SF-6D utility was 0.52 (95% CI 0.48, 0.55). There was no statistical relationship between HIV indices, substance misuse and EQ-5D and SF-6D utility. Anxiety and depression were significantly correlated with EQ-5D and SF-6D utility values on univariate and multivariate analysis. Health-related quality of life was reduced in this HIV-infected intravenous drug user population. Whilst hepatitis C co-infection and substance misuse did not affect health-related quality of life, anxiety and depression had a significant impact on it.